The use of performance measurement in universities. Issue 2 (6th March 2017) - Alach, Zhivan
Abstract : Purpose: The purpose of this paper is to identify the degree of maturity in performance measurement in a national group of universities. Design/methodology/approach: A model for identifying the level of performance measurement maturity in an organisation was identified; this model consisted of seven constructs. A survey consisting of Likert-scale items derived from the maturity model was then administered to academic and administrative staff at New Zealand's eight universities. Findings: The survey showed a relatively high use of performance measurement (usage index 3.47/5), and strong alignment of strategy and performance measurement (strategy index 3.95/5). Research output measures were the most commonly used by academics, whereas measures relating to community service and third role activities were used least. Multiple significant differences between academics and administrators were identified, with the degree of support for performance measurement a particular area of contrast. The overall degree of performance measurement maturity identified was higher than found in similar studies utilising documentary methods. Originality/value: Performance measurement in higher education is a controversial subject and there has been relatively little research into the basics of how, and how well, universities utilise the approach. This exploratory study helps fill the gap and provides a basis for more detailed research.